FORENSIC ACCOUNTING IN FRAUD PREVENTION AND MANAGEMENT: A SYSTEMATIC LITERATURE REVIEW - Alfiana Wanda Lestari; Sinta Febriani (Jurnal Magister Akuntansi Trisakti, 2026)
This study systematically reviews the contribution of forensic accounting to fraud prevention and detection, with a particular focus on its role in strengthening anti-fraud mechanisms in Indonesia. The research adopts a systematic literature review (SLR) approach to analyze 26 journal articles published between 2015 and 2025. The selected studies consist of national journals indexed in SINTA (levels 1–6) and international journals indexed in Emerald Insight, ensuring a balanced integration of local and global perspectives. The findings reveal that forensic accounting plays both reactive and proactive roles in addressing fraud. In its reactive capacity, it supports post-fraud investigation, evidence collection, and litigation processes. Meanwhile, its proactive role is reflected in the utilization of advanced technologies, such as big data analytics, artificial intelligence, and digital forensics, as well as the implementation of forensic audits to enhance early detection and prevention mechanisms. The study also identifies a significant shift from a traditional post-fraud investigative approach toward a more strategic and preventive orientation in organizational anti-fraud frameworks. Theoretically, this study contributes to filling gaps in the Indonesian forensic accounting literature by providing a comprehensive and integrative analysis of existing research. Practically, the findings emphasize the importance of strengthening auditor competence, improving regulatory frameworks, and fostering cross-functional collaboration among organizational units. However, this study is limited to secondary data sources; therefore, future research is recommended to incorporate empirical methods, particularly in high-risk sectors and digital audit practices, to enhance the robustness and applicability of the findings.